Derivation and characterization of putative embryonic stem cells isolated from blastoderms of Taiwan Country chicken for the production of chimeric chickens. Issue 5 (3rd October 2022) - Amporn, Chalothon; Tang, Pin-Chi; Wang, Chien-Kai
Abstract: The conservation of Taiwan Country chicken (TCC) is important due to concerns for the local breed's adaptability to the area and disease resistance. Furthermore, the genetic resource base of native chickens can be used to improve egg and meat production efficiency in commercial TCC. As the embryonic stem cells (ESCs) hold great potential for regenerative medicine and species conservation, the aims of this study were to isolate and characterize ESCs of TCC. The blastodermal cells (BCs) were isolated from the zona pellucida of stage X chicken embryos and cultured in conditioned medium for the proliferation and maintenance of BCs in vitro . The quantitative real-time polymerase chain reaction (qPCR) results showed that POUV, SOX2 and NANOG were expressed in the putative ESCs. In addition, the expression of pluripotent markers, SSEA-1 and SSEA-4, was detected. The DiI-stained ESCs were injected into the dorsal aorta of the E3.5 recipient fetuses soon after staining and the injected embryos were continuously incubated and checked on day 7 of incubation. It was shown that some DiI-positive cells were found in the 7-d-old chimeric embryos. The results demonstrated that some pluripotent cells existed in the cultured BCs for the production of germline chimeric embryos from TCC.